Surviving monotony and repetitiveness at Hawthorne Works: the case of Geraldina “Jennie” Sirchio (1907-1992) and the other migrant girls in the test-room - Salerno, Silvana (La Medicina del Lavoro, 2020)
Background: The research studies in the test room (t-room) at the Hawthorne Works still represent a «mythical» experiment, the most important one. In 1928 the experiment took flight with the Italian Geraldina Sirchio. Objectives: Reporting the living and working conditions of Geraldina and young migrants. Methods: The 22 interviews with Geraldina (1931-1932) conducted by Igemon Rousseau were acquired from Cornell University. The original video of the work in the t-room was analyzed with the method of organizational congruencies. Results: Geraldina left school to work at the age of 14. At 21 she was asked to work in the t-room. She was the fastest girl, unmarried and the “breadwinner” of her family. She was petite, smart and emancipated. Working conditions in the t-room were less challenging than in the “big department” and Geraldina defended them by guaranteeing continuity and very high productivity. In the interviews, she often reported constraints such as low wages, high speed, short breaks, back pain, heat, swollen feet, weight loss and the fainting of girls for “heat prostration”. The interviewer always attributed Geraldina work-related problems to her housework duties. In June 1932, during the last interview, Geraldina expressed her anger for the layoffs, particularly on behalf of the other Italian Antoinette Parillo and the Polish Theresa Layman, both fired despite having to support families with numerous children. She herself was fired five months later. Conclusions: The “Geraldina’s effect” is discussed through her own words offering a truthful picture of the migrant working conditions during the Great Depression.